The Sundanese Traditional Cuisine Proper Names As Home Civilization of Cultural Sustainability: A Cognitive Semantic Study - Elvi Citraresmana; Lusi Susilawati; Hermandra Hermandra (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The researchers convince that the essence of proper names is one of civilization of cultural sustainability. Therefore, we investigated the Sundanese traditional cuisine’s proper names in this article to discuss how proper names are important to be documented well in our inherent traditional cuisine. The proper names are the data collected from the restaurants located in Sukabumi, Garut, and Bandung. The research method applied is a qualitative one. Through a Cognitive Semantic study, the researchers will investigate the phonological sounds and morphological processes that appeared in the Sundanese cuisine’s proper names using conceptualization in line with Cognitive Semantics. Cognitive understanding uses four guiding principles: conceptual structure is embodied, the semantic structure is conceptual structure, meaning representation is encyclopedic, and meaning construction is conceptualization (Evans, Bergen, and Zinken, 2007). The research revealed that the two and three vocal sound combinations appear in the Sundanese food proper names. Furthermore, the acronym also happens in this food's proper names, considering the sound that could produce the exciting names. The name comes from Javanese, but Sundanese people add the morpheme into the first syllables since Sundanese people are familiar with three syllables (Djajasudarma, 2013). Sundanese people name their food based on how the body reacts to a specific action. The form of Sundanese food’s proper name comes from the vocal sounds, which experience a morphemic process—the vocal sounds result in the rhyme. The consonant also tends to form a conceptual meaning that needs further discussion.